Perancangan UI/UX Platfrom NACL Entertainment sebagai Wadah Kreatif Digital Masyarakat dengan Figma Menggunakan Metode Design Thinking - Nadea Cipta Laksmita; Agus Purwanto; Haryoko Haryoko; Rizki Kana Maulana (Syntax Idea)
The development of digital technology has created opportunities for communities to collaborate and express creativity through online platforms. This study aims to design the user interface (UI) and user experience (UX) of the NACL Entertainment platform as a creative hub for society, supporting activities in arts, culture, and innovation. The research adopts the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. The empathize stage involved collecting data through interviews and surveys to understand user needs and challenges. In the define stage, the collected data was analyzed to formulate the core problems to address through the platform design. The ideate stage generated various creative solutions, which were then visualized in the prototype stage using Figma. The resulting prototype was tested during the test stage to gather user feedback and refine the design. The findings indicate that the Design Thinking approach can produce a responsive, intuitive UI/UX design that aligns with the needs of creative communities. The NACL Entertainment platform is expected to become a digital ecosystem that fosters collaboration, creativity exploration, and the growth of arts and culture communities.